Service Providers’ Knowledge and Perceptions of the Legal Service Needs of Crime Victims - Bouffard, Leana A. (American journal of criminal justice, 2017)
Currently, there is an expansive body of victimization literature within the criminal justice field, which covers a number of essential topics such as victimization trends and patterns, short-and long-term effects of victimization, as well as specific effects of intimate partner violence and sexual assault victimization. Despite the variety of topics examined by empirical research, there is a noticeable lack of discourse pertaining to civil legal services for crime victims. This study is among the first to take a close look at civil legal services for victims by exploring three uncharted areas including: (a) service providers’ knowledge of civil legal services, (b) the legal needs of crime victims and available services, and (c) barriers between victims and accessing civil legal services. Using quantitative and qualitative data from interviews with service providers, policy implications and future research recommendations are discussed.